Age-dependent shifts in root resource allocation strategies of Pinus yunnanensis seedlings under variable light gradients - Yuanxi Liu; Guihe Duan; Junwen Wu; Rui Shi (Frontiers in Plant Science, 2025)
To elucidate how seedling age affects shade adaptation mechanisms in Pinus yunnanensis, we conducted a light intensity experiment with 1- and 3-year-old seedlings under five light levels (100%, 80%, 45%, 30%, and 5% of full sunlight). We evaluated the root non-structural carbohydrates (NSC), carbon:nitrogen:phosphorus (C:N:P) stoichiometry, and biomass allocation using phenotypic plasticity indices and correlation analysis. Phenotypic plasticity analysis revealed distinct age-dependent strategies: 1-year-old seedlings prioritized root morphological features (biomass, surface area) and starch storage, whereas 3-year-old seedlings prioritized metabolic flexibility (soluble sugar/starch ratio, N/P balance). Correlation analyses further demonstrated age-specific resource allocation patterns; in 1-year-old seedlings, biomass was associated with the root C/P ratio and starch reserves, whereas in 3-year-old seedlings, growth was associated with soluble sugars and N metabolism. Investment in photosynthetic organs (needle biomass) was prioritized under shade in 1-year-old seedlings, which is consistent with the source-sink theory; however, the root C content of these seedlings was reduced, and their N uptake was enhanced to maintain chlorophyll synthesis. Conversely, survival was prioritized in 3-year-old seedlings by increasing the amount of structural C in roots and optimizing C:N:P stoichiometry (e.g., lower C/N ratio and higher N/P ratio), which is consistent with the C storage priority hypothesis. These findings highlight a developmental transition from growth-driven C allocation in young seedlings to survival-oriented stoichiometric adjustments in older seedlings, which provides important insights for silvicultural practices in heterogeneous light environments.